Biopower and eugenics practice through fertility control in low-income families - Noor Alya Desianty Anthony (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2026)
One policy plan in West Java aims to limit the reproductive agency of poor families that are deemed unable to support their children’s needs by forcing men to undergo a vasectomy to access social assistance. This research aims to examine how neoliberal anti-poverty policies are reflected in contemporary forms of biopower and eugenics practice of fertility control in low-income families. Through qualitative methods with framework analysis using the problem analysis tool “What’s the Problem Represented to be?” by Bacchi, this research argues that neoliberal approach to poverty has justified the state’s attempt to domesticate structural poverty issues. This idea not only opposed the notion that structural factors had caused poverty but also normalized familialism, thereby exempting the state from its responsibilities while burdening families with additional duties. These efforts, along with the practice of gender governance from the central government, as reflected in the Maternal and Child Welfare law, will potentially exacerbate the patriarchal culture and women’s subordination within the gendered division of labor. This research concludes that conducting targeted fertility control as a poverty weapon will neither address the root of poverty nor the gender inequality problems. Instead, this approach will further marginalize low-income families in West Java.